Methanol response of V171S lipase from Geobacillus sp. 42 explored via experimental and in silico approaches - Mohd Johan, Ummie Umaiera; Ishak, Siti Nor Hasmah; Latip, Wahhida; Raja Abd Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Leow, Adam Thean Chor; Mohamad Ali, Mohd Shukuri (Springer Science and Business Media Deutschland GmbH, 2025)
The stability of lipase in organic solvents is crucial for biocatalytic processes in industrial biotechnology. Previously, we described a thermostable and solvent-tolerant Lip 42 from Geobacillus sp. Despite these features, the wild-type Lip 42 activity deteriorated and became unstable in methanol at high temperatures, limiting its effectiveness in solvent-driven catalysis. This study aims to integrate experimental data with molecular dynamics simulation, free energy landscape (FEL), and principal component analysis (PCA) to explore the structural and dynamic properties of V171S mutant lipase, in aqueous and methanol environments. Optimal conditions were determined at pH 8.0 and 70 °C, with notable thermal stability at 65 °C. Importantly, V171S exhibited solvent tolerance, maintaining over 70% relative activity in methanol, ethanol, acetone, 1-propanol, heptanol, octanol, and n-hexane. To further evaluate its performance in methanol, comparative in silico analyses were performed against the wild-type lipase. Structural analysis revealed that V171S maintained stability with only minor fluctuations compared to the native Lip 42 in methanol condition at 65 °C. Root mean square fluctuation (RMSF) analysis highlighted increased flexibility in the lid 1 region, suggesting structural adaptation to solvent exposure. The principal component analysis demonstrated that Lip 42 adopted broader structural distributions in methanol compared to the V171S variant. Free energy landscape analysis confirmed the presence of distinct and stable energy minima for V171S in methanol. Collectively, V171S mutation improves structural integrity under methanol stress, especially at high temperatures. This study contributes to the development of robust biocatalysts that function efficiently in mixed-solvent systems operating at elevated temperatures, especially in the field of biodiesel production.